HUBUNGAN MOTIVASI BELAJAR DENGAN KEGIATAN PEMBELAJARAN PESERTA DIDIK KELAS VIII DI SMP NEGERI 17 PADANG - Fitria, Wike - (Bimbingan dan Konseling, 2014)
Education has an important role in shaping the character of a nation that there areeducators and learners in it. While students are often seen come late to school, get out whenlearning activities held, do not listen when the teacher explains the lesson and do not make the taskthat given by the teacher, lazy in learning, did not participate in class, as well as learners are notindependent in the task given. It is shown that learners are not motivated to learn and interfere withlearning activities. This research describes the motivation of learners, learning activities andrelationships of students learning motivation and learning activities in class VIII students of SMPNegeri 17 Padang. The type of research is descriptive research with quantitative statistical analysiscorrelation with the population of class VIII students of SMP 17 Negeri Padang with thepopulation of 249 students in 71 samples. The sample that used was simple random technique. Theinstrument used for data collection in the form of a questionnaire. To analyze the data of learningmotivation and learning activities of learners using the kriterium Sturgess, while testing thehypothesis on the relationship between learning motivation and learning activities of learners usingthe Pearson Product Moment Correlation formula. The result of the study are: (1) the motivation oflearners are at strong enough category. (2) the learning activities of students in quite well category.(3) The relationship between learning motivation and learning activities of students.